OS FILHOS BRANCOS DA FÉ DE NEGRA RAIZ: UM ESTUDO ANTROPOLÓGICO EM UM TERREIRO DE CANDOMBLÉ DE CAMPO GRANDE – MS - GABRIEL PEREIRA GARCIA (2023)
A racially stratified country like Brazil, the significant number of individuals practicing the Candomblé religion constitutes a phenomenon that challenges the established social order. Our experience within the Candomblé community revealed a predominantly white ethnic-racial composition, prompting an exploration into the phenomenon of Candomblé whitening and its intersections with issues such as whiteness within the dynamics of the Afro-diasporic religious experience. This study engages with the anthropology of Afro- Brazilian religions and employs psychoanalytic theories on whiteness to conduct field research at the Axé Nascente terreiro in Campo Grande, MS. The research involved participant observation by a native ethnographer and semi-structured interviews. Contrary to initial perceptions, the analysis suggests that the terreiro is less whitened than anticipated, yet influenced by manifestations of whiteness, particularly through external priests and the broader societal impact of urbanization. Conversely, an examination of the symbolic universe within the Afro-diasporic cosmology of Candomblé, as expressed in ritual practices, reveals an ontological force shaping individual identity and discourse— referred to as "blackness." Despite the presence of whiteness, the terreiro emerges as an educational space actively countering whiteness through the transformative power of blackness.